ANALYSIS CLAIM BPJS REVIEW FROM COMPLETENESS OF MEDICAL RECORD DOCUMENTS AND ACCURACY DIAGNOSIS CODES IN RSUD. dr. ISKAK TULUNGAGUNG - Sukiatun Sukiatun (Journal for Quality in Public Health, 2017)
Hospitals to document incomplete information, it is possible that the diagnostic codes are also inaccurate and have an impact on the cost of health services. The inaccuracies of the diagnostic codes and the completeness of the medical record will affect data and report information that ultimately affects the patient. The objective of the research was to analyze the BPJS Claim in terms of Document Record and Document Diagnosis Accuracy at RSUD dr. Iskak Tulungagung. The research design used was observational analysis. The study population was All Medical Record Document Inpatient BPJS patients in RSUD dr. Iskak Tulungagung. The sample size ware 140 by using systematic random sampling technique. Independent variable of research is Document Record and Document Diagnosis Accuracy. The dependent variable was BPJS Claims. Data was collected using Check list, then the data were analyzed using logistic regression with a significance level of α ≤ 0.05. The result showed that have the most medical record documents are incomplete resume as many as 52,1%, most have anaaccurate diagnosis code as much as 58,6% and the majority of escape document claims after verification by BPJS officials as many as 78,6%. Results logistic regression analysis obtained by vulue off overall statistics (p) 0,794, which means that documents medical records and the accuracy of diagnosis codes did not affect claims BPJS. There are several factors that make BPJS claims that are not all medical records are subject to BPJS claims, complete medical record documents but still require clarification, any diagnosis if the code may be included on the INA CBG's software and in certain cases a copy of the investigation, action and evidence of medical device is required.